2010
DOI: 10.1186/1742-2094-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute paretic syndrome in juvenile White Leghorn chickens resembles late stages of acute inflammatory demyelinating polyneuropathies in humans

Abstract: BackgroundSudden limb paresis is a common problem in White Leghorn flocks, affecting about 1% of the chicken population before achievement of sexual maturity. Previously, a similar clinical syndrome has been reported as being caused by inflammatory demyelination of peripheral nerve fibres. Here, we investigated in detail the immunopathology of this paretic syndrome and its possible resemblance to human neuropathies.MethodsNeurologically affected chickens and control animals from one single flock underwent clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 86 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…Nobody has shown conclusive evidence that autoreactive T-cell response is observed in patients with GBS, indicating that EAN is not a true model of AIDP [26]. Like AIDP and EAN, inflammatory demyelinating polyradiculoneuropathy in avian is characterized by infiltration of nerve roots and peripheral nerves with macrophages and lymphocytes and, most importantly, a cell-mediated demyelination [23,24] that supports our present findings. A bird from 15th and 20th PID had no lymphocytic infiltration but prominently axonal degeneration with some paranodal demyelination.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Nobody has shown conclusive evidence that autoreactive T-cell response is observed in patients with GBS, indicating that EAN is not a true model of AIDP [26]. Like AIDP and EAN, inflammatory demyelinating polyradiculoneuropathy in avian is characterized by infiltration of nerve roots and peripheral nerves with macrophages and lymphocytes and, most importantly, a cell-mediated demyelination [23,24] that supports our present findings. A bird from 15th and 20th PID had no lymphocytic infiltration but prominently axonal degeneration with some paranodal demyelination.…”
Section: Discussionsupporting
confidence: 84%
“…The birds who developed GBS-like symptoms presented with variable pathological findings. Recently, Bader et al [23] reported the paretic phase of avian inflammatory demyelinating polyradiculoneuritis resembles the late-acute phase of human AIDP and is characterized by severe demyelination of peripheral nerves associated with multifocal endoneurial infiltration of lymphocytes and macrophages [23]. In the present study, teased nerve fiber preparations in experimental chickens showed the severe degenerative changes that included perinodal and/or patchy demyelination, Wallerian-like degeneration at the peak of the disease; whereas incomplete remyelination of the fibers was observed during the recovery phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of juvenile chickens in neurological research recently has been emphasized by the highly prevalent GBSlike avian inflammatory demyelinating polyradiculoneuropathy (AvIDP) (Bader et al, 2010) as well as in previous work on inflammatory polyneuropathies (Bacon et al, 2001). These potentially overlapping syndromes and the classical form of Marek's disease Stevens et al, 1981) provide naturally occurring alternatives to experimental animal models for human inflammatory demyelinating polyradiculoneuropathies (IDPs).…”
Section: Introductionmentioning
confidence: 99%